Experimental Study of Mechanical Properties of Unidirectional Woven Carbon Fiber and Fiber Glass - Epoxy Composites - Awla, Naznaz Jalal; Khdir, Younis Khalid (Al-Nahrain Journal for Engineering Sciences, 2023)
In this study, the mechanical properties of an epoxy, unidirectional woven carbon and fiberglass composite were investigated experimentally. ASTM used for preparing the composite specimen. Different ranges of mixing ratios of woven carbon and fiberglass with epoxy are studied. Tensile, impact and bending test are carried out to investigate the mechanical properties for produced new composites. After testing the mechanical properties of the specimens, it is noted that adding of unidirectional woven carbon layers will leads to strengthens the samples. The mechanical properties of woven carbon composite are far superior to those of woven carbon composite with fiberglass.